2018
DOI: 10.1007/s00192-018-3621-7
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of rolled fortified vaginal flap operation on female patients with intrinsic sphincteric deficiency: 2-year follow-up

Abstract: The RFVF operation has a success rate of 90% after a 24-month follow-up. It significantly improved the quality of life of women with SUI due to ISD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Condition-specific questionnaires are reliable tools to assess degree of improvement after medical or surgical treatments [12]. The short form of UDI-6 is a questionnaire which assesses QoL and symptom distress for UI in women [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Condition-specific questionnaires are reliable tools to assess degree of improvement after medical or surgical treatments [12]. The short form of UDI-6 is a questionnaire which assesses QoL and symptom distress for UI in women [25].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that autologous transobturator MUS is safe and effective in the short term. Tension-free vaginal flap (TVF) operation has been proven to be successful in treatment of SUI in females; however, it has a theoretical risk of bladder and urethral injury due to retropubic passage of the passers [11, 12].…”
Section: Introductionmentioning
confidence: 99%